Crystal structure and properties of Al2O3-Cr2O3 solid solutions with different Cr2O3 contents. Issue 2 (1st February 2018) - Zhao, Pengda; Zhao, Huizhong; Yu, Jun; Zhang, Han; Gao, Hongjun; Chen, Qi
Abstract: To enable the comprehensive application of Al2 O3 -Cr2 O3 solid solutions, the crystal structures and properties of Al2 O3 -Cr2 O3 solid solutions with different Cr2 O3 contents were studied. It was observed that Al2 O3 and Cr2 O3 form a complete substitutional solid solution over the entire composition range at 1650 °C, with no compounds being formed. Lattice parameters "a" and "c" both increase linearly with an increase in the Cr2 O3 content. The doping of the Cr 3+ ions causes a more severe lattice strain in the c-axis direction. The diffraction angles of the diffraction peaks decrease in a linear manner with the increase in the Cr2 O3 content. The relationship between the theoretical density of the solid solution and the Cr2 O3 content could be fitted using a second-order polynomial. It was also observed that the linear expansion coefficient of the solid solutions decreases with an increase in the Cr2 O3 content.